Cancer therapy's impact on lipid metabolism: Mechanisms and future avenues - Bhatnagar, Roshni; Dixit, Neal M.; Yang, Eric H.; Sallam, Tamer (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerotic cardiovascular disease is a growing threat among cancer patients. Not surprisingly, cancer-targeting therapies have been linked to metabolic dysregulation including changes in local and systemic lipid metabolism. Thus, tumor development and cancer therapeutics are intimately linked to cholesterol metabolism and may be a driver of increased cardiovascular morbidity and mortality in this population. Chemotherapeutic agents affect lipid metabolism through diverse mechanisms. In this review, we highlight the mechanistic and clinical evidence linking commonly used cytotoxic therapies with cholesterol metabolism and potential opportunities to limit atherosclerotic risk in this patient population. Better understanding of the link between atherosclerosis, cancer therapy, and cholesterol metabolism may inform optimal lipid therapy for cancer patients and mitigate cardiovascular disease burden.